2020
DOI: 10.1088/1757-899x/805/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of silver nanoparticles using leaf extract of Hyptis suaveolens (L.) Poit for environmental and biomedical applications

Abstract: Aqueous leaf extract of Hyptis suaveolens was investigated to synthesize silver nanoparticles (Hs-AgNPs). Biomolecules such as phenolics, proteins, carbohydrates and esters facilitated bioformation of Hs-AgNPs with ƛmax at 420 nm. The nearly spherical Hs-AgNPs were polydispersed and sized 29.19-52.27 nm with yield of 85.8 %. Hs-AgNPs showed potent inhibition of 75.22-100 % against multidrug resistant bacteria, and fungal growth inhibition of 73.33-100 %. Hs-AgNPs scavenged DPPH and H2O2 by 77.75-83.19, and 54.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…There was no change in the spectra even after 24 h which indicates that the reaction came to equilibrium at 24 h. Interestingly the solution was extremely stable even after 24 h, with no evidence of aggregation of particles. These observations corroborated with the previous report [34] on H. suaveolens dried leaf extract based reduction of silver and stabilization of AgNPs. Previously, rapid synthesis of AgNPs with Boswellia ovalifoliolata plant extract was reported in 10 minutes and Shorea tumbuggaia plant extract took 15 min [35] .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…There was no change in the spectra even after 24 h which indicates that the reaction came to equilibrium at 24 h. Interestingly the solution was extremely stable even after 24 h, with no evidence of aggregation of particles. These observations corroborated with the previous report [34] on H. suaveolens dried leaf extract based reduction of silver and stabilization of AgNPs. Previously, rapid synthesis of AgNPs with Boswellia ovalifoliolata plant extract was reported in 10 minutes and Shorea tumbuggaia plant extract took 15 min [35] .…”
Section: Resultssupporting
confidence: 93%
“…[24,39] Recently AgNPs ranging about 29.5 nm to 52.27 nm were synthesised using the dried leaves extract of H. souveolens. [34] Size of the AgNPs synthesized using Cyprus pangorei extracts ranged about 32-60 nm [40] and with Cycas leaf extracts ranged about 2-6 nm. [41]…”
Section: Transmission Electron Microscopy (Tem) and Edaxmentioning
confidence: 98%
“…Ekennia, Anthony C., et al reported the formation of spherical silver nanoparticles using Euphorbia sanguinea and its photocatalytic degradation of CR (90% within 1 h) [208]. In the period of 2019-2020, several publications reported Silver nanoparticles synthesized using leaf extract of various plants, e.g., Borago officinalis [209], Tragopogon collinus [210], Melia azedarach [211], Mentha aquatica [212], Ziziphus joazeiro [213], Elytraria acaulis [214], Hyptis suaveolens [215], Caesalpinia pulcherrima [216], Gomphrena globosa [217], Plumbago auriculata [218], Cucumis prophetarum [219], Polygonatum graminifolium [220], Cocos nucifera [221], Mimosa albida [222], Capparis zeylanica [223], Holoptelea integrifolia [224], Annona Reticulatal [225], Combretum erythrophyllum [226], Berberis vulgaris [227], Catharanthus roseus [228], Ganonerion polymorphum [229], Premna integrifolia L [230], and Piper betle [231]. Roots are also well established for the synthesis of silver nanoparticles, as shown in Table 13.…”
Section: Synthesis Of Silver Nanoparticles Using Leaf Extracts: (2019-2020)mentioning
confidence: 99%
“…Different AgNPs formulations are available in the market differing in shape, size distribution, the content of metallic silver, synthesis procedure, surface functionalization, and coating agent of the nanoparticles [16][17][18]. All these features help nanoparticles to reach and interact with a wide range of biological targets, playing a significant role in the cytotoxic effects exerted [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%